Architectural profiling of Negeri Sembilan Malay Traditional House: Rumah Bolompa / Fazlin Awaludin ... [et al.] - Awaludin, Fazlin; Mohd Nor, Othman; Abd Rashid, Mohd Sabrizaa; Awaludin, Farahidatul Akmar (2021)
Negeri Sembilan Malay Traditional House (NSMTH), a unique character, is facing gradual vanishing threats from its generation’s uniqueness ownership as well as cultural and built environment values. Rumah Bolompa, one of the types of Negeri Sembilan Malay traditional houses, is faced with an extinction threat since it has been abandoned by the local people. This study aims to explore and investigate the characteristics of Rumah Bolompa and present the findings of an inclusive literature review. The literature review is one of the research activities which aimed to resolve the originality of Negeri Sembilan traditional houses. Thus, the findings of this study point to the increasing difficulty in maintaining the identity and uniqueness of the traditional houses of Negeri Sembilan, and the lack of clarity which can be understood by today's generation.